Estudio Hidrogeológico Del Sector “Caliata” Mediante Tomografías Eléctricas De Resistividad - Sánchez Chicaiza, Víctor Hugo (2023)
The research work was carried out in a specific area of the parish called Flores, Caliata community, belonging to Riobamba, based on stratigraphic and hydrogeological studies of the subsoil for subsequent mathematical modeling in two dimensions (2D) and three dimensions (3D) with Res2Dinv and Voxler 4, determining the area of the aquifer for groundwater conservation purposesin the sector. For the application of the geophysical and hydrogeological methods, it was taken into account that the terrain does not have a pronounced relief and that there are no constructions; the accessibility and climatic conditions were verified, also using GPS equipment that determined the geographical location of the electrodes with which the SYSCAL equipment works. As the realization of the electrical tomographies in two dimensions (2D), the first step was to place the electrodes on the ground at the same distance (5m) in a straight line; once the equipment was installed, the data reading began automatically. In addition, four tomographies were performed showing the lithological materials found in the area and the presence of a subway aquifer; the data obtained were entered into the Res2Dinv software to perform a data inversion, and after this, modeling in the Voxler 4 software for the generation of the 3D model in three dimensions. The electrical tomographies present resistivity ranges from 1.08 to 2652 Ohm*m, representing the lowest resistivities permeable zones that can conduct or store the water resource and the highest resistivities impermeable soils, sands, rocks, etc. In addition, the generation of the 2D images allowed us to identify and interpret that in the chosen study area, there is a semi-confined aquifer located at a depth of approximately 40 meters deep and surrounded by semi-permeable lithological material. With the help of 3D modeling, the semiconfined aquifer and the different subsoil materials covering it were observed better, and it was possible to identify how to act to conserve this groundwater